Structural Change and the State of the Labour Market in Sri Lanka - Karunaratne, H.D. (My University, 2012)
This paper investigates causes of trends and structural changes in labour market in Sri Lanka during 1963-2006 period. Total labour force has increased nearly three times while generating slow growth in employment during the past fifty years. Unemployment rate had been prevailing at higher level until late 1970s. Main reasons behind the drastic decline of it in 1990s have been the sizable slowdown in population growth since 1970s, high international migration rate, expansion of education levels, and urban informal sector economic activities after 1977. None of these factors have been directly contributing to increase output in the economy. Contrary, significant structural changes in employment, unemployment and underemployment have been undergone in terms of gender, age, education level, sector, industry and profession. Finally, labour market has operated by creating many push factors for international migration such as low real wages, high unemployment and underemployment rates, discriminations in terms of gender, age, sector, industry, profession and level of education.